Numerical Simulation of the Tsunami Generated by a Potential Submarine Landslide in La Palma (Canary Islands) after the September 2021 Cumbre Vieja Eruption - Raúl Periáñez (Geosciences, 2021)
Cumbre Vieja volcano, located in La Palma Island (Canary Islands, Spain), erupted on 19 September 2021. Some papers have been published in the past in which the tsunamis generated by a potential massive landslide due to a collapse of one of the volcano flanks are investigated. However, a potential slide of the lava flow down the island slope has not been considered yet. A numerical model has been applied to simulate the propagation of the tsunami generated by such slide and to assess its consequences in the near field (Canary Islands and west coast of Africa). The model provides maps of maximum wave heights and arrival times of the tsunami, as well as time series of water surface elevation at several selected locations. Since the volume involved in such potential slide is a priori not known, several values were tested and their effects compared.